ПІДВИЩЕННЯ ЗНОСОСТІЙКОСТІ СКЛАДНОПРОФІЛЬНИХ ДІЛЯНОК АЛМАЗНО-ГАЛЬВАНІЧНОГО ШАРУ ПРАВЛЯЧОГО ІНСТРУМЕНТУ КОМБІНУВАННЯМ CVD- ТА HPHT-АЛМАЗІВ - SHEIKO, M.; LAVRINENKO, V.; RYABCHENKO, S.; SOLOD, V. (PH “Akademperiodyka”, 2025)
Introduction. At machine-building enterprises in Ukraine, imported guide rollers with SVD diamonds have been used for straightening modern abrasive wheels designed for grinding complex-shaped rotating surfaces. Chemical Vapor Deposition (CVD) represents a contemporary technique for laboratory production of diamond products through chemical vapor deposition, offering promising applications.Problem Statement. During the grinding process with conventional diamond grinding tools, dispersed abrasive material actively erodes the bond in areas where synthetic monocrystalline diamonds are embedded. This results in the premature loss of diamonds before fully utilizing their resource. The elongated shape of SVD diamonds and their deeper embedment in the bond should enhance retention on the working surface, thereby increasing the lifespan of the dressing tool.Purpose. This study aims to optimize the diamond-abrasive layer of the tool by electroplating a mixture of CVD and HPHT (High Pressure High Temperature) diamonds to improve the wear resistance of the tool’s complex-profile sections.Materials and Methods. Diamond powders derived from CVD and HPHT diamonds have been used. The elemental composition of impurities and inclusions in the powders has been analyzed using a BS-340 scanning electron microscope and a Link-860 energy-dispersive X-ray spectrum analyzer. Results. The experimental data have demonstrated that integrating CVD inserts into the high-load areas of the dressing tool significantly enhances the dimensional stability of the working profile. Additionally, the wear patterns of CVD diamonds, as well as HPHT crystals, under abrasive wheel dressing conditions with a ceramic bond, have exhibited characteristics of abrasive wear.Conclusions. The incorporation of directionally improved complex-profile sections with a mixture of CVD and HPHT diamonds in the tool significantly enhances the efficiency and durability of diamond-electroplated dres sing tools.